(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
World experience shows that a vertically integrated system in the textile industry can be efficient and competitive, encompassing processes ranging from the production and initial processing of cotton raw materials to its subsequent processing at cotton mills and transformation into finished products.